Optimalisasi Pengelolaan Keuangan Koperasi untuk Pemberdayaan Ekonomi Masyarakat Desa di Cibinong Bogor - Rudy Rahwana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research was conducted to obtain information related to the ability of cooperative management to be able to optimize the scale of cooperative business, through efficient, productive and rational capital allocation; utilization of business capacity and cooperative capital; cooperation with various parties, both in the form of business, capital and cooperative management in general; and fertilization of own capital, through member savings and the formation of reserve funds. To achieve the above optimization, the stigma of